2013
DOI: 10.1002/iub.1163
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of cataract development in WNIN‐obese rats due to accumulation of intralenticular sorbitol

Abstract: Epidemiological studies have reported an association between obesity and increased incidence of ocular complications including cataract, yet the underlying biochemical and molecular mechanisms remained unclear. Previously we had demonstrated accumulation of sorbitol in the lens of obese rats (WNIN/Ob) and more so in a related strain with impaired glucose tolerance (WNIN/GR-Ob). However, only a few (15-20%) WNIN/Ob and WNIN/GR-Ob rats develop cataracts spontaneously with age. To gain further insights, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…However, no experimental studies have explained the association between IGT and cataract along with their plausible pathophysiological mechanisms. Previous studies from our group have shown that obesity [ 18 , 19 ] as well as prediabetes [ 20 ] is associated with increased susceptibility to cataract formation due to the activation of sorbitol pathway in experimental animals. Thus, there is a need to understand the mechanism of cataractogenesis during IGT as well as T2D.…”
Section: Introductionmentioning
confidence: 99%
“…However, no experimental studies have explained the association between IGT and cataract along with their plausible pathophysiological mechanisms. Previous studies from our group have shown that obesity [ 18 , 19 ] as well as prediabetes [ 20 ] is associated with increased susceptibility to cataract formation due to the activation of sorbitol pathway in experimental animals. Thus, there is a need to understand the mechanism of cataractogenesis during IGT as well as T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Between Ob and GR-Ob animals, the latter accumulated twice the quantity of sorbitol in the tissue. It also showed a critical level of 650 nmoles/g tissue of sorbitol will result in cataract formation, and this was found to be true when sorbitol levels were measured in animals that showed cataract in vivo 46. Galactose-induced and STZ-induced diabetes was studied in three-month-old Ob and GR-Ob rats, and it was seen that the stage of cataract and onset were faster in obese animals compared to that of lean controls.…”
Section: Highlights Of Recent Studies In Wnin/ob Ratsmentioning
confidence: 89%
“…It was still intriguing as to why only 20 per cent of the rats developed cataract and for this, susceptibility of lenses of obese and lean rats to develop cataract was studied using environmental [heat and ultraviolet (UV) irradiation] and physiological insults (glucose mediated, hyperglycaemia in vivo ). Heat and UV-induced aggregation studies46 showed that the light-scattering ability of lens-soluble proteins was high in six month and 12 month old obese rats than in lean animals. While lens opacification by glucose in lens organ culture ex vivo required seven days in lean animals, this was accomplished in four days in obese lenses.…”
Section: Highlights Of Recent Studies In Wnin/ob Ratsmentioning
confidence: 99%
“…In addition, obesity directly or indirectly influences the osmotic stress and nonenzymatic glycation of lens proteins [4]. A recent study found that intralenticular sorbitol accumulation beyond a threshold level leads to the increased risk of cataract formation in WNIN-obese rats [5]. Finally, obesity is potentially linked to ARC secondary to its comorbid cardiometabolic conditions, including diabetes [6], dyslipidemia [7], and hypertension [8], which themselves are known risk factors of ARC [9,10].…”
Section: Introductionmentioning
confidence: 99%